Impact of Successful HCV Eradication on Glycemic Control in Chronic HCV Patients with Type II Diabetes Mellitus - Sehrish Sarwar, Israr Ul Haque, Junaid Mushtaq, Azhar Ali Khan, Atif Qureshi, Hafiz Hamad Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Chronic HCV infection has been implicated as a risk factor for new onset diabetes mellitus type II and worsening of glycemic control in patients with already established Diabetes due to defined molecular mechanisms. The impact of successful HCV eradication with direct-acting antiviral agents (DAAs) on glycemic control in HCV patients with concomitant Diabetes mellitus is being assessed by several studies but still unclear due to scarce data in literature, which specifically address this aspect of DAAs. Objective: To study the impact of successful HCV eradication with DAAs based regimes on glycemic control in a cohort of Chronic HCV patients with concomitant Type II Diabetes Mellitus. Materials and Methods Study design: Descriptive Case series Study place: Department of Gastroenterology, Lahore General Hospital, Lahore. Duration: Six months i.e. 15-2-2021 to 15-8-2021 Data collection procedure: 110 patients, who fulfill the inclusion, were enrolled in the study.All patients of Hepatitis C received DAAs in the form of Oral Sofosbuvir 400 mg and Oral Daclatasvir 60 mg daily for 12 weeks without Ribavirin. Only Child Pugh class A and class B patients were included. Before starting treatment glycosylated haemoglobin (HbA1c) and Viral load by HCV RNA polymerase chain reaction was also checked. All the patients were followed at the end of treatment i.e. at 12 weeks( from the baseline ) and then three months after treatment (at 24 weeks), for viral load testing by HCV RNA polymerase chain reaction and HbA1c levels. Results: In this study 91% patients achieved sustained virological response and 83% of the patients achieved improved glycemic control after successful HCV eradication. Age (23-33: 16.5%, 34-44: 40.7%, 44-54: 29.7% p-value=0.728) and gender (Male: 39.6% & Female: 60.4%, p-value=0.142) have no significant association with glycemic control of patients. Conclusion: Based on the findings of this study, it can be concluded that oral DAAs can help improving the glucose levels and glycemic control significantly in HCV patients with concomitant Type II diabetes mellitus and successful HCV eradication can prevent the long term complications of diabetes and may need dose reduction for insulin therapy in these patients